HUMAN RIGHTS PROTECTION MECHANISMS: INTERNATIONAL STANDARDS AND NATIONAL PRACTICE OF KAZAKHSTAN - Zhamankarayeva , Galiya Seitkarimovna; Matayeva , Maigul Khafizovna; Maishekina , Eldana Sovetovna (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
This article investigates how international human rights monitoring bodies affect domestic human rights systems through an examination of the Republic of Kazakhstan. The research investigates the ongoing discrepancy between Kazakhstan’s international legal commitments and its domestic human rights standard implementation. The study investigates international human rights oversight mechanisms as its main subject while analyzing Kazakhstan’s responses to UN Human Rights Committee and Committee against Torture and Universal Periodic Review (UPR) recommendations through institutional and legal frameworks. The research evaluates the impact of international monitoring systems on domestic legal and institutional changes and determines the elements which influence their execution. The study uses a combination of comparative legal analysis, teaching studies and institutional methods for studying specific situations, as well as data from United Nations documents, Kazakh legal sources, scientific publications and civil society reports. This article shows that Kazakhstan has achieved progress through treaty ratification and Ombudsman institution creation, yet practical execution remains restricted. The fundamental obstacles regarding freedom of expression together with association rights and movement freedom and domestic violence protection continue to exist. The success of international monitoring depends on political will together with independent institutions and active civil society involvement. The research adds to knowledge about transnational legal influence and provides useful recommendations to boost national compliance. Its results provide valuable information to policymakers together with legal scholars and human rights advocates who want to boost international monitoring effectiveness in hybrid or transitional legal systems.